2019
DOI: 10.1111/cge.13507
|View full text |Cite
|
Sign up to set email alerts
|

Deep phenotyping of 14 new patients with IQSEC2 variants, including monozygotic twins of discordant phenotype

Abstract: Whole‐exome sequencing has established IQSEC2 as a neurodevelopmental disability gene. The IQSEC2 variant phenotype includes developmental delay, intellectual disability, epilepsy, hypotonia, autism, developmental regression, microcephaly and stereotypies but is yet to be fully described. Presented here are 14 new patients with IQSEC2 variants. In addition to the established features, we observed: gait ataxia in 7 of 9 (77.8%), drooling in 9 of 14 (64.2%), early feeding difficulties in 7 of 14 (50%), structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 27 publications
6
31
0
Order By: Relevance
“…IQSEC2 gene mutations were previously reported in families with X-linked ID. 2,3 Recent literature has shown that IQSEC2 mutations cause a neurodevelopmental disorder with many features starting early in life. [3][4][5]7 The IQSEC2 gene is placed on chromosome Xp11.22 and its product, the BRAG1 protein, is located on the excitatory synapse as a part of the Nmethyl-D-aspartic acid receptor complex, and plays a role in synaptic plasticity and dendritic spine formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IQSEC2 gene mutations were previously reported in families with X-linked ID. 2,3 Recent literature has shown that IQSEC2 mutations cause a neurodevelopmental disorder with many features starting early in life. [3][4][5]7 The IQSEC2 gene is placed on chromosome Xp11.22 and its product, the BRAG1 protein, is located on the excitatory synapse as a part of the Nmethyl-D-aspartic acid receptor complex, and plays a role in synaptic plasticity and dendritic spine formation.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Recent literature has shown that IQSEC2 mutations cause a neurodevelopmental disorder with many features starting early in life. [3][4][5]7 The IQSEC2 gene is placed on chromosome Xp11.22 and its product, the BRAG1 protein, is located on the excitatory synapse as a part of the Nmethyl-D-aspartic acid receptor complex, and plays a role in synaptic plasticity and dendritic spine formation. 8 These proteins are required for trafficking of α-amino-3-hydroxyl-5-methyl-4-isoxazolepropionic acid receptors from the surface of hippocampal neurons, thus playing an important role in learning and memory processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The challenges such as incompleteness, inaccuracy and complexity have been much discussed (Hripcsak and Albers, 2013). Many studies of deep phenotyping focused on a set of phenotypic features defined based on expert knowledge of specific diseases or medical issues (Kopf et al, 2018;Peron et al, 2018;Radley et al, 2019) (Greene et al, 2016). In our study, the EHRs are in French language, thus the annotation is achieved with UMLS French (SAP=FRE) in our data warehouse.…”
Section: Comparison To Other Workmentioning
confidence: 99%